POLICE MISCONDUCT ON THE HIGHWAY OF TEARS: MISSING AND MURDURED INDIGENOUS WOMEN AND GIRLS IN BRITISH COLUMBIA (Canadian Journal of Native Studies, 2026)
This exploratory study examines ‘The Highway of Tears’ casesin Northern British Columbia. Qualitative interviews withlocal Indigenous Peoples and Elders on the Highway of Tearsprovide empirical data to inform the issue of Missing andMurdered Indigenous Women and Girls (MMIWG) in Canada.This research demonstrates the systemic and multi-facetedracism that continues to marginalize and oppress IndigenousPeoples. Such discrimination exists within Canadiansociety and the organizational structure of the Royal CanadianMounted Police. This research uses organizational and environmentalapproaches to police deviance and interviewswith First Nations to contribute to understanding why theMMIWG cases are under-investigated and remain unsolved.